Water migration in unsaturated partially hydrophobic soils (2017)
This article presents new insights into effects of hydrophobic particles on water migration in fine graded soils. The experimental setup for this study uses a column of soil instrumented with sensors that allows direct measurements of soil water content at different heights of the column during capillary rise, infiltration under imposed pressure and drainage. To precisely determine the proportion of hydrophobic particles the fine grained soil was mixed with microparticles of Teflon (PTFE). The water retention curve was measured for mixtures with three different percentages of hydrophobic particles: 0%, 2%, and 5% by weight. In addltion, the water repulsion curve of the PTFE particles was measured using a water intrusion test. This test showed high water repellency that modifies the unsaturated characteristics of the mixtures. Results of this study show a huge effect of hydrophobic particles on capillary rise, but water repellency decreases when pressure is imposed and becomes relevant again during the drainage process. This study provides a new survey that could be useful for understanding the benefits and limitations of soil treatments with hydrophobic chemical products.